2013
DOI: 10.1001/jamasurg.2013.2701
|View full text |Cite
|
Sign up to set email alerts
|

Use the Duodenum, It’s Right There

Abstract: Duodenal anastomosis is a safe, simple, and often preferable method for biliary reconstruction. This anastomosis can successfully be performed to all levels of the biliary tree with low rates of leak, stricture, cholangitis, and bile gastritis. When anastomotic complications do occur, there is less need for transhepatic intervention because of easier endoscopic access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Secondly, data from liver transplant patients and experience from our transplant center have shown that HD gives satisfactory results [13, 14]. Others have found excellent results with HD that are comparable with HJRY in a variety of indications such as benign bile duct strictures, choledochal cysts, HPB-cancer, and bile duct injuries [1518]. A recent report advocated HD as the preferred method of biliary reconstruction and described it is as a safe and simple technique with low rates of leak, stricture, cholangitis, and bile gastritis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, data from liver transplant patients and experience from our transplant center have shown that HD gives satisfactory results [13, 14]. Others have found excellent results with HD that are comparable with HJRY in a variety of indications such as benign bile duct strictures, choledochal cysts, HPB-cancer, and bile duct injuries [1518]. A recent report advocated HD as the preferred method of biliary reconstruction and described it is as a safe and simple technique with low rates of leak, stricture, cholangitis, and bile gastritis [17].…”
Section: Discussionmentioning
confidence: 99%